MODELING OF DISPLACEMENT PROCESSES IN HETEROGENEOUS ANISOTROPIC GAS RESERVOIRS - Lubkov, M.; Zaharchuk, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Nowadays there are important problems of increasing efficiency of development and exploitation of gas deposits. There are problems associated with the growth of gas production in heterogeneous anisotropic reservoirs, increasing gas recovery, achieving economic efficiency and so on. In this situation, there are popular methods of computer modeling of gas productive reservoirs, because they allow getting information of the structure and characteristics of the gas reservoir, the distribution parameters of permeability and other important factors in it. They also allow evaluating and calculating uncertainty arising from the lack of information about the gas reservoir properties outside the well. Currently there are many methods of computer modeling, allowing solving various practical problems. From another hand there are some problems related to the accuracy and adequacy of simulation of heterogeneous anisotropic permeable collector systems in real conditions of gas deposits exploitation. On the base of combined finite-element-difference method for solving the nonstationary anisotropic piezoconductivity Lebenson problem, with calculating of heterogeneous distribution of permeable characteristics of the gas reservoir, we carried out modeling of filtration processes between production and injection wells. The results of computer modeling show that intensity of the filtration process between production and injection wells depends essentially on their location both in a shifting-isotropic and anisotropic gas reservoir. Therefore, for the effective using of poorly permeable shifting-isotropic gas-bearing reservoirs, it is necessary to place production and injection wells along the main anisotropy axes of the gas-bearing layers. At the placing production and injection well systems in low-permeable anisotropic reservoirs of a gas field, the most effective exchange between them will take place when the direction of increased permeability of the reservoirs coincides with the direction of the location of the wells. Obviously, the best conditions for gas production processes in any practical case can be achieved due to optimal selection of all anisotropic filtration parameters of the gas reservoir. One can use obtained results for practical geophysical works with a purpose optimizing of gas production activity in low-permeable heterogeneous anisotropic reservoirs. Presented method for more detailed investigation of low-permeable heterogeneous anisotropic gas-bearing deposits can be used.